Report on the breakage of the tip of a radial endobronchial ultrasonic probe sheath during bronchoscopy. Issue 4 (28th February 2018) - Yaguchi, Daizo; Ichikawa, Motoshi; Inoue, Noriko; Kobayashi, Daisuke; Shizu, Masato; Imai, Naoyuki
Abstract : Bronchoscopic biopsy using an ultrasonic probe with a guide sheath to confirm that the target lesion is reached is an established and routine procedure, but familiarity with the possible breakage of related devices is important. We experienced breakage of the tip of the ultrasonic probe sheath of a bronchoscope. Careful investigation concluded that the tip did not break off during the examination, but rather broke and was lost during cleaning after the examination. Abstract : A lesion in a 73‐year‐old woman that was suspected to be right lung cancer was biopsied under ultrasound‐guided bronchoscopy with a guide sheath. The procedure was completed without a noticeable problem, but after 3 days, it was found that the tip of the ultrasonic probe sheath was broken and that the broken fragment was missing. Based on the concern that the fragment had been left in the lung, the patient was examined by computed tomography scan 4 days after the biopsy, and bronchoscopy was repeated 38 days after the biopsy, but no fragment was detected. These procedures and an investigation by the Olympus Corporation led to the conclusion that the fragment was not in the lung, and it was not found in a subsequent surgical specimen. Breakage of devices may occur at any time regardless of progression of fatigue (wear) with increased use, and thorough device management before, during, and after use is important.